Fishing for conservation of freshwater tropical fishes in the Anthropocene. Issue 7 (29th April 2019) - Phang, Sui Chian; Cooperman, Michael; Lynch, Abigail J.; Steel, E. Ashley; Elliott, Vittoria; Murchie, Karen J.; Cooke, Steven J.; Dowd, Scott; Cowx, Ian G.
Abstract: The ecosystem services provided by freshwater biodiversity are threatened by development and environmental and climate change in the Anthropocene. Here, case studies are described to show that a focus on the shared dependence on freshwater ecosystem functioning can mutually benefit fisheries and conservation agendas in the Anthropocene. Meeting the threat to fish biodiversity and fisher livelihood is pertinent in developing regions where there is often a convergence between high biodiversity, high dependency on aquatic biota and rapid economic development (see Kafue River, Logone floodplain, Tonle Sap, and Rio Negro case studies). These case studies serve as evidence that biodiversity conservation goals can be achieved by emphasizing a sustainable fisheries agenda with partnerships, shared knowledge and innovation in fisheries management (see Kafue River and Kenai River case studies). In all case studies, aquatic biodiversity conservation and fisheries agendas are better served if efforts focused on creating synergies between fishing activities with ecosystem functioning yield long‐term livelihood and food security narratives. A unified voice from conservation and fisheries communities has more socio‐economic and political capital to advocate for biodiversity and social interests in freshwater governance decisions.